ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN SEPEDA MOTOR YAMAHA (STUDI PADA DEALER YAMAHA PT. UTAMA MEGAH SENTOSA BERSAUDARA) - Situmorang, Yohanes Lorens; Ferdinand, Augusty Tae (Diponegoro Journal of Management, 2017)
Transportation needs of motorcycles in Indonesia is increasing from year to year. And this is an opportunity for companies that offer motorcycle products to increase sales figures in various ways. This study aims to determine the effect of service quality product innovation, customer value and competitive pricing on purchasing decisions Yamaha brand motorcycles in the city Banjarbaru (a case study on consumer Yamaha Dealer "PT UTAMA MEGAH SENTOSA BERSAUDARA" )This study uses five variables: service quality, product innovation , customer value, competitive price and purchasing decisions. This research hypothesis testing using the data of 100 respondents. The analysis technique used in this research is to use a software program Statistical Package for Social Science (SPSS) 22.The result of this study indicate that variable service quality and product innovation positively affect to customer value. Then, costumer value and competitive price are positively affect to purchase decision.